Pilgrimage in Graeco-Roman & early Christian antiquity : seeing the gods - Elsner, Jaś; Rutherford, Ian, 1959- (Oxford University Press, 2005)
This book is an innovative collection of seventeen essays by leading scholars of ancient religion on aspects of pilgrimage in Greek and Roman and Early Christian Antiquity. The period covered is roughly from 500BC till 400AD, and the types of pilgrimage studied is very broad, ranging from state delegations that are more or less politically motivated to the journeys of individuals interested in intellectually or spiritual enlightenment. Essays are arranged in three sections: Part 1 (‘Classical and Hellenistic Pilgrimage’) comprises six essays, dealing with aspects of Greek state-pilgrimage (‘theōria’), as well as the representation of pilgrimage in literature and philosophy; Part II (‘Pilgrimage in the Roman Empire’) contains seven essays dealing with topics such as healing pilgrimage, cultural pilgrimage by elites and pilgrimage in oriental cults; finally Part III (‘Jewish and Christian Pilgrimage’) comprises four essays dealing with inter alia, Jewish and Christian pilgrimage to Jerusalem, and Christian pilgrimage in Egypt in Late Antiquity. The essays are preceded by an Introduction in which the editors discuss the appropriateness of the term ‘pilgrimage’ to this period, arguing against scholars who have suggested that the term should not be used when dealing with polytheism; they also set out a typology of twenty forms of pilgrimage attested in this period.